2015
DOI: 10.1521/aeap.2015.27.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Post-Exposure Prophylaxis (PEP) and Pre-Exposure Prophylaxis (PrEP) Is Low but Interest Is High Among Men Engaging in Condomless Anal Sex With Men in Boston, Pittsburgh, and San Juan

Abstract: This study examines awareness of and experiences with post-exposure prophylaxis (PEP) and pre-exposure prophylaxis (PrEP) among 228 men recruited in Boston, Pittsburgh, and San Juan between 12/2010–6/2012. All of them reported having condomless anal sex with a man in the prior year. Overall, 41% had heard of PEP, ranging from 16% in San Juan to 64% in Boston. Only 21% had heard of PrEP, ranging from 8% in San Juan to 36% in Boston. Three had used PEP, and none had used PrEP. After the methods were described to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
4
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 22 publications
4
76
4
3
Order By: Relevance
“…Condoms were the most frequently preferred method in the paired preference test. This is surprising given the well-documented rates of incorrect and inconsistent condom use among MSM (40, 41), but may be related to extensive familiarity with condoms and low awareness of PrEP among these study participants, as also reported in other research (42, 43). …”
Section: Discussioncontrasting
confidence: 55%
“…Condoms were the most frequently preferred method in the paired preference test. This is surprising given the well-documented rates of incorrect and inconsistent condom use among MSM (40, 41), but may be related to extensive familiarity with condoms and low awareness of PrEP among these study participants, as also reported in other research (42, 43). …”
Section: Discussioncontrasting
confidence: 55%
“…Awareness of PEP (88.3%) was higher than expected based on previous research. In samples of HIV-negative MSM in the United States, awareness of PEP has ranged from 41.0% (Dolezal et al, 2015) to 47.0% (Liu et al, 2008). This level of awareness is also higher than those observed in samples of MSM in Australia (Zablotska et al, 2011), Canada (Lin et al, 2016), Italy (Prati et al, 2016), and Spain (Fernández-Balbuena et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, health departments throughout the country have been promoting PrEP uptake among populations at risk of HIV, often through demonstration projects. While there are some notable successes in PrEP implementation, particularly among MSM of higher educational and socioeconomic status, uptake among minority communities lags behind (Dolezal et al, 2015; Hood et al, 2016; Martinez, Wu et al, 2016). Research on factors associated with differential PrEP uptake among minorities, including gender minority Latinx, is urgently needed to reduce their lifetime HIV risk (Lelutiu-Weinberger & Golub, 2016).…”
Section: The Promise Of Pre-exposure Prophylaxis (Prep)mentioning
confidence: 99%
“…However, among Latinos with limited English proficiency, awareness is considerably lower. Only 8% of MSM in Puerto Rico were aware of PrEP compared to 64% of MSM in Boston (Dolezal et al, 2015). …”
Section: Barriers To Prep Uptake Among Sexual and Gender Minority Latmentioning
confidence: 99%